Pathways and Mechanisms of Cellular Cholesterol Efflux—Insight From Imaging - Juhl, Alice Dupont; Wüstner, Daniel (Frontiers in Cell and Developmental Biology, 2022)
Cholesterol is an essential molecule in cellular membranes, but too much cholesterol can be toxic. Therefore, mammalian cells have developed complex mechanisms to remove excess cholesterol. In this review article, we discuss what is known about such efflux pathways including a discussion of reverse cholesterol transport and formation of high-density lipoprotein, the function of ABC transporters and other sterol efflux proteins, and we highlight their role in human diseases. Attention is paid to the biophysical principles governing efflux of sterols from cells. We also discuss recent evidence for cholesterol efflux by the release of exosomes, microvesicles, and migrasomes. The role of the endo-lysosomal network, lipophagy, and selected lysosomal transporters, such as Niemann Pick type C proteins in cholesterol export from cells is elucidated. Since oxysterols are important regulators of cellular cholesterol efflux, their formation, trafficking, and secretion are described briefly. In addition to discussing results obtained with traditional biochemical methods, focus is on studies that use established and novel bioimaging approaches to obtain insight into cholesterol efflux pathways, including fluorescence and electron microscopy, atomic force microscopy, X-ray tomography as well as mass spectrometry imaging.